2018
DOI: 10.1016/j.joca.2018.02.227
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy can non-invasively distinguish between ochronotic and non-ochronotic cartilage

Abstract: Purpose: Alkaptonuria is a rare genetically inherited form of OA which is characterised by urine which darkens on standing, pigmentation of articular cartilages and early-onset, rapidly progressing osteoarthropathy of multiple weight bearing joints. The pigmentation is caused by presence of a tyrosine metabolite; homogentisic acid (HGA), which polymerises over time to for a pigment in the articular cartilages. The presence of pigment changes the biochemical and biomechanical properties of the cartilage causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The ear cartilage biopsy showed that ochronosis was not uniform throughout the sample and this heterogeneity is a limitation in its usefulness. A non‐invasive analysis is being developed by utilizing Raman Spectroscopy for a future study, 25 in which a much larger area of the ear tissue could be analyzed. The appearance of ear and eye ochronosis coincides with the appearance of low back and knee pain, suggesting a common evolving ochronotic pathogenetic process 2,3 …”
Section: Discussionmentioning
confidence: 99%
“…The ear cartilage biopsy showed that ochronosis was not uniform throughout the sample and this heterogeneity is a limitation in its usefulness. A non‐invasive analysis is being developed by utilizing Raman Spectroscopy for a future study, 25 in which a much larger area of the ear tissue could be analyzed. The appearance of ear and eye ochronosis coincides with the appearance of low back and knee pain, suggesting a common evolving ochronotic pathogenetic process 2,3 …”
Section: Discussionmentioning
confidence: 99%